2021
DOI: 10.30880/jtet.2021.13.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation Trends in Vocational Education in Indonesia During the COVID-19 Pandemic

Abstract: The COVID-19 Pandemics has forced the changes of many aspects of life, including vocational education. Schools must adapt to the a new condition of learning activities towards online learning. However, online learning becomes more challenging for vocational schools that focus on practical lessons. The limited access to the internet and technological tools in many remote and rural areas also become main issues in delivering the learning activities. Therefore, teachers and schools need to offer various learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In Indonesia, school accountability is developed by the central government [18], [19]. The form of school accountability can be seen in various nationally applicable education standards [20]. Digital transformation can be a driving force for better standardization.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, school accountability is developed by the central government [18], [19]. The form of school accountability can be seen in various nationally applicable education standards [20]. Digital transformation can be a driving force for better standardization.…”
Section: Introductionmentioning
confidence: 99%
“…Digitalization in education continues to experience developments that affect patterns and strategies in learning, learning systems that have changed to electronic learning, which is a model that uses technology in the learning process [6,7]. Various media can be used in the learning process, digital media, mobile learning, audio-visual media, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In July 2021, China released the 2020 National Research Report on minors' Internet use, which showed that 93.6% of minors studied through online classes during the COVID-19 pandemic. Similarly, the proportion of the online completion of higher education in China was relatively large [2].…”
Section: Introductionmentioning
confidence: 99%
“…What are the characteristics of regulation focus under the influence of intervention scripts? (2). What are the levels and behavioral characteristics of CKB under the influence of intervention scripts?…”
Section: Introductionmentioning
confidence: 99%